Importance of the layered structure of leaves on the determination of their scattering and absorption properties - Corinna Konrad; Markus Wagner; Florian Foschum; Alwin Kienle (Science of Remote Sensing)
The influence of the layered structure of plant leaves on the optical properties obtained with a homogeneous theoretical model was investigated. To this aim, silicone phantoms with different optical properties modeling synthetic leaf layers were fabricated to study a two-layer model of the leaf. The optical properties were determined with spectrally resolved integrating sphere measurements using solutions of the radiative transport equation for a homogeneous medium. When the optical properties of a two-layer stack were retrieved, they showed large differences from the optical properties of the involved single layers depending, in addition, on the orientation of the two-layer stack in the measurements. We also obtained the optical properties of a Taraxacum officinale leaf with a homogeneous theoretical model and compared them to those retrieved from a two-layer forward model using Monte Carlo simulations. The optical properties obtained from the simulations showed similar features of the optical properties retrieved from the measurements, including the difference when changing the orientation of the leaf. Therefore, our model is able to provide an explanation for the found effects.